An analysis of trends, frequencies and factors influencing the development of resistance to phosphine in the red flour beetle Tribolium castaneum (Herbst) in Australia. (May 2017) - Nayak, Manoj K.; Falk, Matthew G.; Emery, Robert N.; Collins, Patrick J.; Holloway, Joanne C.
Abstract: Although resistance to phosphine, the key disinfestant used worldwide in the stored grain environment has been an ongoing industry issue, studies on its trend over large geographic region and over long period of time is very limited. In this study, we critically analysed 20 years' phosphine resistance diagnosis data for the red flour beetle Tribolium castaneum (Herbst) stored in the Australian Grain Insect Resistance Database. Resistance diagnosis on a staggering 6336 samples, along with information on storage types and treatment history was interrogated to establish trends and frequencies of resistance development in this species and factors that may have contributed towards these resistance occurences. Using descriptive statistics, linear and trend analysis and a well established Bayesian hurdle model, we determined that strong resistance in T. castaneum was significantly more prevalent in quarantine intereceptions than in central storages and on farms. The strong resistance incidences had been confined to eastern states of Queensland, New South Wales, Victoria and South Australia, whereas it is yet to be detected in the state of Western Australia. We could not establish any significant correlation between the strong resistance development and any commodity or treatments. After an initial increasing trend in incidences since the first detection of strong resistance in 1997 in this species, the frequency was stabilised during 2001–08; after which there had been an upward trend since 2009 till the last survey in 2013. The conclusions derived from this analyses highlighted the importance of a resistance monitoring program with relevant information being used in Australia as the basis for ongoing and future phosphine resistance management strategies. This research may also proved valuable towards devising similar strategies in overseas countries with phosphine resistance problems. Highlights: Strong phosphine resistance in Tribolium castaneum confined to Queensland, New South Wales, Victoria and South Australia. Strong resistance significantly more prevalent in quarantine intereceptions than in central storages and farms. Upward trend in strong resistance detections since 2009. Analysis of 20 years of resistance monitoring data forms the basis for ongoing resistance management strategies.